Antioxidant Activity of Total phenols and Flavonoids extracted from Echinops polyceras roots grown in Syria - Al-Assaf, Issa; Khazem, Mays (Iraqi Journal of Pharmaceutical Sciences, 2021)
Free radicals are reactive compounds, their excessive production is considered to be an important cause of oxidative damage in biomolecules causing degenerative diseases. Polyphenols are one of the most important groups of secondary metabolites of plants, which have an antioxidant activity depending on their properties as hydrogen donors. Echinops polyceras Boiss. (Asteraceae) is one of Echinops genus species that spread in Syria, Lebanon, and Palestine. Phytochemicals found in this species leaves have been extracted with gradient polarity solvents, and primary screening of the secondary metabolites was established. The phenolic compounds and flavonoids contents were determined. The free radicals scavenging activity was evaluated for all extracts with DPPH• in a 96-well microplate. The specificity study indicates that ascorbic acid was absent, and reducing sugars were exist in the aqueous extract. The identification tests showed the presence of polyphenols like flavonoids and coumarins. The methanolic extract of the E. polyceras leaves was the most effective scavengers of free radicals (90.22% in 30 min) with phenolic compounds content 682.5 mg GAE/g of dried extract (DE) and flavonoids content 194.5 mg QE/ g DE. The chloroform extract was the least effective as free radical scavenging (60% in 30 min) as the phenolic compounds content was 278.5 mg GAE/g DE and flavonoids content 94 mg QE/ g DE. In conclusion, the phenolic compounds and flavonoids from Echinops polyceras Boiss. are effective in free radicals scavenging and protecting from diseases caused by oxidative stress.